Approvisionner Cayenne sous l'Ancien Régime Archéologie et histoire des réseaux commerciaux - Losier, Catherine (Taboui, 2016)
This research documents commercial networks of French Guiana during the Ancien Régime (pre-revolutionary France). The analysis of archaeological collections from six plantation sites and the official correspondence of colonial authorities between 1688 and 1794, provides new insights into the commercial organisation and external links associated with this colony, located on the margin of the circum-Caribbean world. It also discusses the globalisation and interdependency between Europe and the colonies, which are the result of European imperialistic quests. Archaeological analysis offers a novel understanding of French Guiana provisioning. It leads to the identification of important commercial networks linking Cayenne with the Caribbean islands and North-American colonies. During the second half of 18th century, these networks became an alternative to the great East-West commerce, which was so often unsatisfactory to the Cayenne island inhabitants. Archaeological and archival information were combined in order to document the influence of French Guiana on the modern World economy. It shows the settlers' reaction toward French government projects, and the unexpected turns that impact the Atlantic economy beyond the control of the Metropolis. Thus, this research is about the impact of a marginal colony on the Atlantic commercial networks.